213k views
3 votes
F(x) = 3x + 10g(x) = x - 2Find f(g(0))

User Romkey
by
4.9k points

1 Answer

1 vote

For this problem we have the following two functions given:

f(x)=3x+10, g(x)=x-2

And we want to find:


f(g(x))=3(x-2)+10

If we simplify we got:


f(g(x))=3x-6+10=3x+4

After this we can replace x=0 and we find the final result:


f(g(0))=3\cdot0+4=4

So then the final answer for this case would be 4

User Industrial
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.